Fault Severity Evaluation and Improvement Design for Mechanical Systems Using the Fault Injection Technique and Gini Concordance Measure. (30th April 2014) - Wu, Jianing; Yan, Shaoze
Abstract : A new fault injection and Gini concordance based method has been developed for fault severity analysis for multibody mechanical systems concerning their dynamic properties. The fault tree analysis (FTA) is employed to roughly identify the faults needed to be considered. According to constitution of the mechanical system, the dynamic properties can be achieved by solving the equations that include many types of faults which are injected by using the fault injection technique. Then, the Gini concordance is used to measure the correspondence between the performance with faults and under normal operation thereby providing useful hints of severity ranking in subsystems for reliability design. One numerical example and a series of experiments are provided to illustrate the application of the new method. The results indicate that the proposed method can accurately model the faults and receive the correct information of fault severity. Some strategies are also proposed for reliability improvement of the spacecraft solar array.